Presença de material eletrodenso sob a membrana vitelina do ovo de Scaptotrigona postica latr. (Hymenoptera, Meliponinae) durante a fase inicial da embriogenese - Cruz-Landim, Carminda da [UNESP]; Beig, Darvin [UNESP] (Instituto Oswaldo Cruz, Ministério da Saúde, 1989)
The present paper reports the presence of an electrondense material of unknown nature distributed under the viteline membrane of Scaptotrigona postica egg. The dorsal side layer is thicker then the ventral one. In eggs newly oviposited the material is gradually distributed inside the plasmalema invaginations. Later on (12 hs after oviposition) when a blastoderm is already formed around the egg, the material moves to the intercellular space. on the sequence of the development there was no more indication of the material under the membrane.
Presence of electrodense material under the viteline membrane of Scaptotrigona postica Latr. egg (Hymenoptera, Meliponinae) during the embryogenesis initial fase
Keywords: bee; Meliponinae; Embryogenesis; Hymenoptera